The Existence of Friday Charity Activities at Al-Muhajirin Mosque, Perumnas, Tihu Subdistrict, Ambon City - Ichwan Firdaus; Yunus Rahawarin; Jeffry Ernest Marthen Leiwakabessy (Universitas Pattimura, 2026)
This qualitative research aims to find out, understand, and explain the existence of blessing Friday in the form of eating together rather than symbols and meaning based on views or perspectives resulting from the construction of orientation, life experiences, and through the process of social interaction carried out by the worshippers of Al-Muhajirin Mosque as a manifestation of building social solidarity. The research was conducted at Al-Muhajirin Perumnas Mosque in Tihu Village, Ambon City. The data is taken from the primary source. The sampling technique used purposive sampling. Data were collected by the methods of interview, observation, and documentation. The data analysis technique uses three stages such as data reduction, data presentation, and conclusions. The results showed that each individual who participated in the Friday blessing activity, namely eating together, had different points of view or perspectives in giving symbols and meanings to the meal together in the mosque. The existence of these activities forms a harmonious life in the midst of cultural diversity and creates a sense of social solidarity through the process of social interaction that is intertwined in eating together at the Al-Muhajirin Mosque. The form of social solidarity that is built in the blessed Friday activity is unity with fellow individuals because of the same values and emotional feelings, having a more intense deviation in working together and helping in goodness who are experiencing difficulties in terms of college problems, economic problems, to health problems. If someone is experiencing difficulties, each other helps each other by giving a little money for college and food needs, providing blood donor assistance for those who are sick, this raises a strong sense of solidarity through social relationships formed in the blessed Friday activity at the Al-Muhajirin Mosque.